The Shi‘a Position Toward the Three Rightly Guided Caliphs (May Allah Be Pleased with Them) Through Their Method of Interpreting the Qur’an by the Qur’an: A Theological Study - Al-Damigh, Huda Abdullah; Al-ʿOtaibii, Sahl Raffāʿ (Journal of Islamic Sciences, 2025)
This study examines the Imami Shiʿa’s position toward the three Rightly Guided Caliphs - Abū Bakr, ʿUmar, and ʿUthmān (may Allah be pleased with them) - through their approach to interpreting the Qur’an by the Qur’an. Objectives: The research aims to examine the Twelver Shi‘a’s position on the first three Caliphs by analyzing their Qur’anic exegesis, highlighting doctrinal and methodological deviations in their interpretations that seek to undermine the legitimacy of the Companions and the consensus of the Prophet’s community. Methodology: An inductive-deductive approach was adopted, collecting all instances in which the Twelver Shi‘a interpreted the Qur’an in reference to the three Caliphs. These instances were critically analyzed in light of the methodology of Ahl al-Sunnah and the exegesis of Sunni scholars to assess the validity of their interpretations. Results: The study found that the Twelver Shi‘a deliberately manipulate Qur’anic texts, imposing interpretations contrary to the apparent meaning and linguistic context, to support their beliefs in discrediting the Rightly Guided Caliphs. It further revealed that the method of interpreting the Qur’an by the Qur’an is only valid when applied according to its proper legal and methodological conditions. Attacking the Companions through this method constitutes a serious deviation from the Prophetic tradition and scholarly consensus, refuted by definitive Qur’anic evidence, Prophetic narrations, and the agreed virtue and justice of the Caliphs. Conclusion: The research emphasizes the importance of presenting the methodology of Ahl al-Sunnah in Qur’anic exegesis, teaching its principles in academic institutions, documenting narrations with their chains and textual analysis, and exposing the distortions of the Twelver Shi‘a with proper refutations to preserve doctrinal purity and methodological soundness.